The language accessible to the citizen and the vulnerable population from the perspective of the 100 Rules of Brasilia - Ato Alvarado, Martín Eduardo (2023)
In this work we will review that, faced with the communicative barrier of incomprehension posed by judicial language, the movement of language accessible to citizens and vulnerable populations arises for their protection. Trend that arose when Englishspeaking countries as a target of Transparency supported the «Plain Language Movement»; and that other countries develop the right to simple language in the government sphere; including people in vulnerable situations. Thus, we will expose its evolution, the Brasilia Rules on simple language, language accessible to citizens and the vulnerable population, inclusive language, easy language, its development and application in Peru and Latin America. We conclude that language accessible to citizens and the vulnerable population contributes to the protection of their rights; and that the Peruvian Judiciary has not consolidated its practice.